1996
DOI: 10.1103/physrevb.54.2381
|View full text |Cite
|
Sign up to set email alerts
|

Abinitioinvestigation of the electronic properties of planar and twisted polyparaphenylenes

Abstract: Ab initio band-structure calculations are carried out on stereoregular polyparaphenylene at the Hartree-Fock level of approximation using the split-valence 3-21G basis set. We investigate the effects due to the torsion angle between adjacent phenyl rings upon the ionization energies and bandwith values, as well as upon the density of states and the uncoupled Hartree-Fock longitudinal polarizability per unit length. From the bandwidth values, it is inferred that solid polyparaphenylene is better represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
6
34
0
Order By: Relevance
“…Correlation corrections reduce the valence and conduction bandwidths to 4.12 and 5.22 eV, respectively. 33 The restricted HF calculation by Champagne et al 37 gave a valence bandwidth of 4.45 eV which is similar to the results of Ladik et al The ultraviolet photoelectron spectroscopy ͑UPS͒ study carried out on solid and gaseous sexiphenyl reported for the valence bandwidths values of 3.5 and 2.9 eV, respectively. 24 Of course to obtain an estimate of mobility, one has to take into account interchain hoppings which may even be dominant.…”
Section: B Band Structuressupporting
confidence: 73%
See 3 more Smart Citations
“…Correlation corrections reduce the valence and conduction bandwidths to 4.12 and 5.22 eV, respectively. 33 The restricted HF calculation by Champagne et al 37 gave a valence bandwidth of 4.45 eV which is similar to the results of Ladik et al The ultraviolet photoelectron spectroscopy ͑UPS͒ study carried out on solid and gaseous sexiphenyl reported for the valence bandwidths values of 3.5 and 2.9 eV, respectively. 24 Of course to obtain an estimate of mobility, one has to take into account interchain hoppings which may even be dominant.…”
Section: B Band Structuressupporting
confidence: 73%
“…Our LDA result for the ionization potential is 4.93 eV whereas the XPS 23 37 using a split-valence 3-21G basis set predicted an ionization energy of 7.16 eV.…”
Section: B Band Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In each unit cell, there are four (CH) 2 groups situated in two polymer chains. The LDA and GGA optimized geometrical parameters, including the bond lengths, the bond angles and the setting angle of the chain as well as the lattice vectors are listed in Table I together with the experimental results [33][34][35] and the other theoretical predictions 36,37,21,24 for both the single chain and the crystalline system. For reasons of numerical stability that will be discussed below, the GGA geometry is actually obtained at a pressure of 0.1 GPa which is sufficiently small in comparison with the pressure steps of 2 GPa used in this article.…”
Section: Geometries Under Zero Pressurementioning
confidence: 99%